An Acquired Factor VIII Inhibitor in a Patient with HIV and HCV: A Case Presentation and Literature Review - S. B. Zeichner; A. Harris; G. Turner; M. Francavilla; J. Lutzky (Case Reports in Hematology)
Introduction. Despite its low incidence, acquired factor VIII inhibitor is the most common autoantibody affecting the clotting cascade. The exact mechanism of acquisition remains unclear, but postpartum patients, those with autoimmune conditions or malignancies, and those with exposure to particular drugs appear most susceptible. There have been several case reports describing acquired FVIII inhibitors in patients receiving interferon alpha for HCV treatment and in patients being treated for HIV. To our knowledge, this is the first case of a patient with HCV and HIV who was not actively receiving treatment for either condition. Case Presentation. A 57-year-old Caucasian male with a history of HIV and HCV was admitted to our hospital for a several day history of progressively worsening right thigh bruising and generalized weakness. CTA of the abdominal arteries revealed large bilateral retroperitoneal hematomas. Laboratory studies revealed the presence of a high titer FVIII inhibitor. Conclusion. Our case of a very rare condition highlights the importance of recognizing and understanding the diagnosis of acquired FVIII inhibitor. Laboratory research and clinical data on the role of newer agents are needed in order to better characterize disease pathogenesis, disease associations, genetic markers, and optimal disease management.